The university’s social responsibility in light of the academic programs ’response to the requirements of the local community - Salima Gaci (Social Empowerment Journal, 2021)
Our research paper came with a descriptive approach coupled with a statistical treatment in which we tried to highlight the role of the university and the contribution of its academic formation in developing social responsibility among its graduates, by investigating the reality of university academic programs responding to the requirements of field practice in the local community from the point of view of a sample of graduates of the Department of Social Sciences At Umm El Bouaghi University, And access to ways to activate the relationship between the university and the service reality in the local community, and accordingly the study problem was identified in the following question: Does university academic training contribute to the development of social responsibility for the student who is a graduate of the Department of Social Sciences?